Perbandingan Analisis Pengendalian Obat Menggunakan Metode EOQ Dan ROP Dengan Tingkat Laba Di Rsia Ananda Lubuklinggau - Effendi, M.; Maya Sari, Wisdalia; Efrianti, Yuli; Azhar, Rudi; Raberta, Yulpa (Jurnal Sains dan Teknologi, 2024)
This study aims to determine the comparison of drug control analysis using the EOQ and ROP methods with profit levels at RSIA Ananda Lubuklinggau. The research conducted is operational research with a qualitative approach. Data collection techniques using observation and interview methods. The analysis technique uses data reduction analysis, data presentation and conclusions. Based on the analysis, the conclusions that can be drawn in this study are 1) Availability of drugs at RSIA there are 6 types of drugs, namely liquid drugs, tablets, capsules, suppositories, injectable drugs and implants. 2) Availability of drugs prior to implementation of the EOQ and ROP methods related to the type and quantity of drugs cannot be sufficient to meet the needs because there are still several drugs which cannot be met in a timely manner to fulfill their needs. 3) Availability of drugs has been implemented by applying the EOQ and ROP methods in the pharmaceutical warehouse when viewed from the type and quantity of drugs that are sufficient to meet the wishes of the pharmaceutical installation in a timely manner.